Klasifikasi Kabupaten/ Kota Sejahtera dan Tidak Sejahtera dengan Metode Spectral Clustering pada Provinsi Sumatera Utara - Batu, Annisa Rajaq Lumban; Lubis, Riri Syafitri; Harleni, Silvia (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
People's welfare is basically a condition whose form is dynamic or in other words its quantitative value will never stop because it will continue to change along with the development of human life needs. In the Regional Medium Term Development Plan (RPJMD) of North Sumatra Province, the government is trying to realize an advanced and prosperous community life. Law No. 11 of 2019 article 3 paragraph 1, it is also written that the purpose of administering social welfare is to increase the level of welfare, quality and survival. As according to the Central Statistics Agency for North Sumatra in 2021 regarding indicators of people's welfare, namely, population, health, education, employment, household consumption and expenditure, housing and the environment, and participation in social activities. To make a strategy to improve the welfare of the people of North Sumatra, the Government needs to determine which districts or cities are prosperous and which are not. This study uses the spectral clustering method in which this method forms clusters obtained according to data taken at the Central Bureau of Statistics which will be carried out in 2022 data taken in 2021. The results of this study indicate the application of the spectral clustering method for classifying prosperous and less prosperous city districts in North Sumatra province and clusters obtained as many as 2 clusters from data from 33 urban districts in North Sumatra province, namely cluster 1 is a prosperous district or city, namely Medan and Deli Serdang, and cluster 2 is a district or city that is not prosperous, namely, apart from Medan and Deli Serdang.